AKT2在非小细胞肺癌中的表达及预后意义 (Zhongguo Fei Ai Za Zhi, 2011)
BACKGROUND AND OBJECTIVE: AKT2 is a critical actor in the PI3K signal transduction pathway. Activation of AKT2 can lead to cell growth and survival. It has been revealed that AKT2 play a central role in tumorigenesis, tumor growth as well as metastasis. The aim of this study is to investigate the association between AKT2 and the clinical outcome of non-small cell lung cancer (NSCLC) patients by detecting its expression levels in the tumor tissue samples. METHODS: We developed an immunohistochemistry (IHC) assay to measure AKT2 protein levels in lung specimens from 80 cases with NSCLC and 10 cases with benign pulmonary disease. RESULTS: The positive rate of AKT2 was 57.50% (46/80) in NSCLC, which was higher than that in benign pulmonary (10.0%) samples (χ(2)=8.038, P=0.006). There was no significant correlation between AKT2 expression and the clinicopathologic profiles. The expression of AKT2 was significantly correlated with the progression free survival (PFS) (χ(2)=12.671, P=0.005) and the overall survival (OS) (χ(2)=9.851, P=0.021) of patients with NSCLC. CONCLUSION: AKT2 may provide a prognostic bio-marker of NSCLC.